ANALISIS KESEJAHTERAAN RUMAH TANGGA PETANI PLASMA KELAPA SAWIT DI DESA RIMBAH JAYA TRAN 500 KECAMATAN PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Purba, Rayzon; Rifa, Ahmad; ', Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are: (1) To analyze the oil palm farm income;(2) Analyze the of structure household income; (3) Analyze the structure of house hold expenditure; (4) Analyze the oil palm small holder welfare in Rokan Hulu regency. The data used are primary data. Amount respondents as many as 30 sample. where there search was conducted in March 2014, results were obtained that the palm oil farm income of Rp39.260.217.33/year/RT, the structure of household income derived from agricultural income of Rp100.651.514/year/RT, and non-farm income of Rp100.8 million/year/RT, the structure of household expenditure is divided into two, namely food and non-food, non-food expenditure where the biggest cost incurred is on rice, while non-food is the cost of education, house hold welfare level at 0 - 3 indicator (7%),indicators 4 – 8 (86%),indicators 9 – 12 (7%) and indicators 13 – 14 (0%). Keywords: Farmers palm, Income, Welfare